THE BUREAUCRATIC-PATRIMONIAL STATE IN GEORGIA: HAS THE “ROSES REVOLUTION” GIVEN IT A NEW LEASE OF LIFE? - APRASIDZE, David (CENTRAL ASIA AND THE CAUCASUS, 2004)
The post-socialist transformation phase that began late in the 1980s was a very special period in the context of the third wave of democratization that started in the 1970s. This was when the eastern military-political bloc headed by the Soviet Union fell apart.1 The post-socialist and especially the post-Soviet phases were marked by systemic transformations when the political system was undergoing the transition from authoritarianism to democracy and when the economic system was experiencing radical changes.